STRENGTH AND DUCTILITY OF REINFORCED CONCRETE T-BEAMS STRENGTHENED IN THE NEGATIVE MOMENT REGION WITH WIRE ROPE AND MORTAR COMPOSITE - Y. Haryanto; I. Satyarno; D. Sulistyo (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2012)
The loss due to collapsing structure includes not only materials but also lives. In the case of a change in structure function that may cause increasing loads, it is required to put efforts in strengthening the structure elements in order to increase the capacity and hence to avoid the possibility of collapsing. The objective of this research is to find out the behavior of T-sectional reinforced concrete beam strengthened in the negative moment region with wire rope and mortar composite. The test was carried out on three T-sectional beams: without wire rope reinforcement (BK), with 2 wire rope reinforcements (BP1), and with 4 wire rope (BP2) reinforcements. The type of wire rope was Independent Wire rope Core (IWRC) with a 10 mm diameter. The testing method used was two points static loading with flens positions below (the flens part experienced tensile stress). Results showed that the maximum load carrying capacity of BP1 and BP2 specimens increased by ratios of 1.59 and 2.03 to the BK specimen, respectively. However, the increase was achieved after the development and propagation of high cracking. Ductility of BP1 and BP2 specimens decreased with a ratio of 0.62 to 0.36 to the BK specimen, respectively. The initial stiffness of BP1 and BP2 increased with a ratio of 1.09 to 1.08 to the BK specimen, respectively. The effective stiffness of BP1 and BP2 specimens decreased with a ratio of 0.88 to 0.92 to the BK specimen, respectively. Stress occurred in the wire rope based on the analysis results of Response-2000 and the layer method did not reach 50% of the ultimate stress resulting from the preliminary test. In general, unless improvement was made to the stiffness characteristics of the wire rope, its contribution would not become optimum. Keyword: Wire rope, mortar, flexural behaviour.